Difficulties of Primary School Students in Mathematics - Kafle, Bhuban; Dahal, Prem Prasad (Janajyoti Journal, 2025)
Students often face difficulties while learning mathematics at primary level. To obtain the obstacles of the students in the mathematical progress and outcomes, this study was conducted systematically. This is the quantitative study with the involvement of 24 students of class two from primary five schools in the Lalbandi municipality. On the basis of result of the Progress Monitoring Test and CAS of respective schools, the students were identified with mathematical difficulties. Students, here participants, were chosen with the help of the quartile (lower quartile or the first quartile (Q1) to involve in the progress monitoring test of the intervention program. After the result of the Progress Monitoring Test, a small group of four participants was chosen for the intervention program to measure the progress of those participants. It was difficult to manage the intervention program with optimal group size. The tests of the intervention program were conducted for seven times with the participants. These tests were taken after every 7 days to measure the progress in number and other mathematical concepts. T-test was used to determine the significant difference between the achievements of the both pre-tests and post-tests. The participants of grade two were found to have faced many types of the mathematical difficulties, viz. low level of understanding, lack of permanent learning, numerical figure confusion, delivery of subject matters and lack of concentrations.